Speed control of DC motor using pole placement controller implementation with PLC - Abdul Latif Aizat, Mohamad Haniff (2008)
Motor speed control is very important in rotating machinery applications. There are many applications that have been developed based on motor speed control theory, such as conveyor. The idea of motor speed control is to take a signal representing the demanded speed, and to drive a motor at that speed. The purpose of this project is to develop the Pole Placement controller to control the speed of DC motor and implement the controller into Ladder Diagram which connected to PLC. By using Pole Placement controller, the DC motor will rotating at the demanded speed which is set by the user with minimum error. Before the controller was developed, numbers of simulations were done using M-FILE (prompt) and MATLAB Simulink. The objective of the simulation is to evaluate the system response of the DC Motor in with and without controller. The used of PLC in this project will help to reduce complexity and made troubleshooting a very easy task to do. The model of PLC which is used in this project is OMRON (CQM1H-CPU51) and the program for this controller system is in ladder diagram (CX Programmer). The Pole Placement controller is implementing in the PLC program so that this system has a better response and less error. Finally, analysis of the response is made after the Pole Placement is implemented into the system.